Iodine‐Promoted Tunable Synthesis of 2‐Naphthyl Thioethers and 1‐Naphthyl Thioethers. Issue 9 (4th April 2019) - Bao, Yishu; Yang, Xiuqin; Dai, Zonghao; Ji, Suyu; Zhou, Qingfa; Yang, Fulai
Abstract: An iodine‐promoted regioselective sulfenylation/deoxygenation/aromatization reaction of 1‐tetralones with disulfides has been developed. This process could be modified to synthesize 2‐naphthyl thioethers and 1‐naphthyl thioethers in moderate to excellent yields, respectively. Furthermore, when the reaction was extended to 2‐tetralones, 2‐naphthyl thioethers were obtained as the sole products. The current study bridges the deoxygenation and sulfenylation/aromatization of ketones, thus providing a new tool in organic synthesis. Abstract :